PEMAKSAAN KONSEP TRIAS POLITICA PADA KEDUDUKAN KOMISI PEMBERANTASAN KORUPSI DALAM SISTEM KETATANEGARAAN INDONESIA - Mashudi Mashudi; Prihatin Effendi; Abdul Basid; Abu Rizal Fadli (UNES Law Review, 2023)
This article analyzes the coercion of trias politica on the KPK's position in the Indonesian constitutional system in Act Number 19-year 2019 concerning KPK, which the author limits to three issues: first, the background of KPK institution in Indonesia, secondly the position of KPK in Indonesia's constitutional system after the revision of the KPK’s Act, and third analysis the KPK's position. This research is normative legal research with statutory approach, conceptual approach, historical approach, and comparative approach. The results show that the background to the existence of the KPK in Indonesia is due to the inability of conventional institutions to resolve corruption, namely the Police and the Attorney General's Office which incidentally are part of the executive. The position of KPK in the state administration system in Indonesia after the revision of the KPK’s Act has been transformed into part of the trias politica concept, namely the executive branch. And the transition of the KPK's position in the state administration system in Indonesia to being part of the Executive clearly imposes the concept of trias politica which is outdated. KPK should remain an independent institution that can be aligned with the trias politica, as many other countries have done.